Erebīana ṭelaśa, eṭale, uṅgamaṇṇa taraphanāṃ loko tathā teonāṃ pāhādaśāhono hevāla aśala Erebīmothī Pharenaca bhaśāmmo ane Pharencamothī Angarejīmo tarajumo thāeloche te ūparathī Gujarāthīmo bhāshānatara kodhāmo āvīūche (Kharaśedajī Barajorajī, 1848)
Selected fairy tales from Arab countries translated from French and English.